2008
DOI: 10.2459/jcm.0b013e3282fb7882
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus-eluting stent implantation for bare-metal in-stent restenosis: is there any evidence for a late catch-up phenomenon?

Abstract: The present study supports the mid-term safety and effectiveness of sirolimus-eluting stents for the treatment of in-stent restenosis in comparison with the other available treatments. Whether the late catch-up phenomenon observed in repeat target revascularization and stent thrombosis is an incidental finding deserves further rigorous scrutiny.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…There have been numerous studies that have shown the relative superiority of DES compared to BMS with regard to in-stent restenosis; however, there has not been a study that has shown superiority with regard to mortality. Furthermore, although it is evident that DES treatment can reduce restenosis or clinically relevant events during the first year compared to the BMS, rate catch-up phenomenon of DESs was reported and repeat target revascularization or stent thrombosis has been increasing [17,18]. We thought that the one case of in-hospital sudden cardiac death in the present study might have occurred due to acute thrombosis.…”
Section: Discussionmentioning
confidence: 65%
“…There have been numerous studies that have shown the relative superiority of DES compared to BMS with regard to in-stent restenosis; however, there has not been a study that has shown superiority with regard to mortality. Furthermore, although it is evident that DES treatment can reduce restenosis or clinically relevant events during the first year compared to the BMS, rate catch-up phenomenon of DESs was reported and repeat target revascularization or stent thrombosis has been increasing [17,18]. We thought that the one case of in-hospital sudden cardiac death in the present study might have occurred due to acute thrombosis.…”
Section: Discussionmentioning
confidence: 65%
“…So, it may appear that mild "angiographic late catch-up" phenomenon does not translate into clinical events. However, another study showed "late catch-up" in repeat target revascularization after SES implantation for bare-metal stent ISR [18]. True clinical implications of "angiographic late catch-up" phenomenon after SES implantation deserves further rigorous scrutiny.…”
Section: Discussionmentioning
confidence: 97%
“…The combination of anti-hyperplasia effect with potent mechanical support for lesion vessel wall in DES yielded a benefit in decreasing the need for repeat revascularization compared with BMS or balloon angioplasty alone during short-term follow-up 30 . Recently, concerns have been raised regarding the "late catch-up" phenomenon in DES, especially with "limus"-eluting stents, in unselected coronary artery diseases 31 . A study by Awata et al using angioscopy showed that SES delayed reendothelialization with immature plaques and accelerated neointimal coverage at 2-year follow-up 32 .…”
Section: Discussionmentioning
confidence: 99%